ANALISIS PENYEBARAN USAHA KECIL DAN MENENGAH (UKM) BERBASIS OLAHAN TANAMAN PANGAN PRODUK UNGGULAN KOTA SINGKAWANG - Sethyo Vieni Sari; Azni Ananda; Sugeng Riyadi (Akademi Farmasi Yarsi Pontianak, 2022)
Small and Medium Enterprises (SMEs) is one that can encourage regional economic development. This research was conducted with the aim of knowing the spread of SMEs, knowing the techniques of processing food crops carried out by SMEs, and the amount of production of SMEs based on processed food crops in Singkawang City. The data were taken by interviewing and filling out questionnaires by the resource persons/respondents. There are 41 SMEs processed food crops which are located in Central Singkawang, West Singkawang, South Singkawang, and North Singkawang Districts, Singkawang City. The East District of Singkawang City did not get data on SMEs based on processed food crops. This is because many SMEs in East District are non-food based. Food crop processing techniques carried out by SMEs in Singkawang City generally process chips using a dry heat processing technique (Dry Heat Of Cooking) by deep frying, which requires a lot of oil so that the food ingredients are submerged. The production of SMEs in Singkawang City ranges from 60 to 24,000 pcs/month, with various processed food crops such as chips, sticks, jam, tofu water, crackers, noodles, and others. The concept of preparing SME products based on processed food plants does not use good preservation, labeling, and marketing techniques. The impact is that product sales are still not optimal.